2016
DOI: 10.1371/journal.pone.0166691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Osteoprotegerin and Dickkopf-Related Protein 1 on Radiological Progression in Tightly Controlled Rheumatoid Arthritis

Abstract: ObjectiveTo analyze the association between circulating osteoprotegerin (OPG) and Dickkopf-related protein 1 (DKK-1) and radiological progression in patients with tightly controlled rheumatoid arthritis (RA).MethodsSerum levels of OPG and DKK-1 were measured in 97 RA patients who were treated according to a treat-to-target strategy (T2T) aimed at remission (DAS28<2.6). Radiologic joint damage progression was assessed by changes in the total Sharp-van der Heijde score (SHS) on serial radiographs of the hands an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Strictly controlled disease activity should improve inflammation associated with RA and thus improve the activities of daily living (ADLs) [ 22 ]. Moreover, improved disease control may contribute to the remodeling of bone metabolism to form normal bone structure not only in the joints but also in the entire body [ 23 ], which will subsequently normalize bone mineral density (BMD). In this study, we investigated if RA is associated with a high risk of osteoporosis even when disease activity is well-controlled by determining if patients with RA have a lower BMD than those without RA.…”
Section: Introductionmentioning
confidence: 99%
“…Strictly controlled disease activity should improve inflammation associated with RA and thus improve the activities of daily living (ADLs) [ 22 ]. Moreover, improved disease control may contribute to the remodeling of bone metabolism to form normal bone structure not only in the joints but also in the entire body [ 23 ], which will subsequently normalize bone mineral density (BMD). In this study, we investigated if RA is associated with a high risk of osteoporosis even when disease activity is well-controlled by determining if patients with RA have a lower BMD than those without RA.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to the small number of RA patients (N = 26) and the healthy group (N = 10) [ 39 ]. Carmen study et al in Spain showed that serum RANKL values were below the detection limit in 85% of RA patients because 76% of them were in clinical remission or in low disease activity [ 40 ]. Our study also found an elevation in RANKL levels in post-menopausal patients compared to post-menopausal healthy group, this confirms its importance in bone loss and pathogenic mechanism of rheumatoid arthritis as found a similar in Çakırca et al study in Turkey [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the discrepancy is that 76% of their patients were in the clinical remission or in the phase of low disease activity, as TNF-α antagonists and some DMARDs used in the RA treatment have inhibited the expression of RANKL by synovial cells 38 . Our study found an elevation in RANKL levels in post-menopausal patients compared to post-menopausal healthy group, this confirms its importance as a biomarker interferes in the bone loss and pathogenic mechanism of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%